Teachers' Narratives for the Liberation of the Identity of the Oppressor Teacher. - Fernández-Torres, Pablo; Calvo-León, Piedad; Martagón Vázquez, Virginia; Rivas-Flores, José Ignacio (My University, 2023)
The study we are presenting shows an experience in which the teacher shares with the students a class diary that is mostly composed of personal reflective processes that happen during the subject. The context in which this experience takes place is in the subject Educational Organisation, in the second year of the degree in pedagogy at the University of Malaga, in the first semester of the academic year 2022- 2023. In this experience, 60 students and the four people who signed this paper participated, three of them being teachers of this subject, and the remaining person teaches the same group, but in another subject. The main objective is to show students the role of the teacher in a more humanised and closer way in order to create a relationship of trust between teachers and students. Paraphrasing bell hooks (2022), in order to create an atmosphere of trust in the classroom it has been necessary to take the teacher out of his or her safety zone, this has been done by not being afraid to show and recognise his or her mistakes, insecurities and even feelings of vulnerability with respect to some topics and situations that arise in class. Following the idea of the same work by bell hooks, conflict situations are used as opportunities to create spaces for debate and critical thinking instead of treating conflicts as taboo situations that are ignored to avoid frustration. The teacher, in this case, shares feelings of satisfaction, frustration, concerns, challenges, and even acknowledges mistakes in the approach to activities that turn out to be contrary to expectations. This generates class discussions in which a process of evolution in classroom interactions can be appreciated. The results of this experience, as well as its consequences, will be shared in the conclusions of this work.
Keywords: Profesores - Formación profesional; Investigación activa en educación; Formación de profesorado; Teacher education; Higher education; Classroom diary; Docencia universitaria; Pedagogía crítica; Critical pedagogy; Diario de clase